Rescuing genetic material of unexpectedly die animal - Syahruddin Said; Takdir Saili (Indonesian Center for Animal Research and Development (ICARD), 2007)
Rat cauda epididymides were kept in 1.5-ml centrifuge tubes containing 1 ml milli-Q water or physiological saline (0.9% NaCl) and stored and freezed at -196ºC without cryoprotectant for up to 7 days. After thawing of the cauda epididymis, all spermatozoa were non-motile immediately after collection. All oocytes injected with sperm heads (nuclei) of spermatozoa collected from frozen-thawed cauda epididymis in saline were activated (100%) and gradually decreased (P<0.05) in cauda epididymis frozen in milli-Q water at -196°C (86%), and in control (69%). In activated oocytes, a large proportion of sperm heads had transformed into male pronuclear formation (66-78%). When 1-cell embryos were cultured for 120 h, 7% developed to blastocyst stages. These results indicate that genetic materials of species (at least in the rat) that had unexpectedly die can be saved by a simple method. Key words: ICSI, Sperm Heads, Piezo-Injection, Frozen, Rat